2006
DOI: 10.1200/jco.2006.06.5664
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional Relapse and Distant Metastasis in Conservatively Managed Triple Negative Early-Stage Breast Cancer

Abstract: Patients classified as triple negative have a poor prognosis. However, there was no evidence that these patients are at higher risk for local relapse after conservative surgery and radiation. Patients with BRCA1 mutations develop predominantly triple negative tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
735
13
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 966 publications
(816 citation statements)
references
References 25 publications
52
735
13
16
Order By: Relevance
“…TNBC is different than other breast cancer subtypes with regard to treatment, because it is not amenable to hormone therapy or anti‐HER2‐targeting therapy, and systemic treatment options are limited to cytotoxic chemotherapy 3, 4, 5. Currently, the primary problem associated with diagnosis of TNBC is judgment of HER2 status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNBC is different than other breast cancer subtypes with regard to treatment, because it is not amenable to hormone therapy or anti‐HER2‐targeting therapy, and systemic treatment options are limited to cytotoxic chemotherapy 3, 4, 5. Currently, the primary problem associated with diagnosis of TNBC is judgment of HER2 status.…”
Section: Discussionmentioning
confidence: 99%
“…Triple‐negative breast cancer (TNBC)—defined as absence of expression of estrogen receptor (ER) and progesterone receptor (PR) as well as no overexpression of human epidermal growth factor receptor 2 (HER2)—accounts for approximately 10% to 20% of all cases of breast cancer 2. TNBC is associated with an aggressive course and poor survival, and unlike patients with ER/PR‐positive or HER2‐overexpressing breast cancer, TNBC is not amenable to hormone therapy or HER2‐targeting therapy, such as trastuzumab 3, 4, 5. Although immunohistochemical (IHC) analysis can be used to assess ER, PR, and HER2 status, some cases of breast cancers are HER2 2+ equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Immunohistochemical marker panels that have been proposed to define basal-like breast cancers include: (1) lack of ER, PR, and HER2 expression ('triple-negative' immunophenotype); (2) expression of one or more high-molecular-weight/ basal cytokeratins (CK5/6, CK14, and CK17); (3) lack of expression of ER and HER2 in conjunction with expression of CK5/6 and/or epidermal growth factor receptor (EGFR); 17 and (4) lack of expression of ER, PR, and HER2 in conjunction with expression of CK5/6 and/or EGFR. 19 Despite the different definitions for basal-like breast cancers, it has been demonstrated that these tumors have distinctive clinical presentations, 20 histological features, 18,21 response to chemotherapy, [22][23][24][25][26][27][28] sites of distant relapse, and outcome. 7,9,[29][30][31] In brief, basal-like tumors comprise a heterogeneous group that accounts for up to 15% of all breast cancers, affect younger patients, are more prevalent in African-American women, and often present as interval cancers.…”
Section: What Is a Basal-like Breast Cancer?mentioning
confidence: 99%
“…The main characteristics of triple-negative cancers that have emerged from the literature illustrate their similarities to basal-like cancers, including the fact that they more frequently affect younger patients (o50 years), 24,30,31,59,61,62 are more prevalent in African-American women, [62][63][64] often present as interval cancers, and are significantly more aggressive than tumors of other molecular subtypes. 24,28,59,[61][62][63] This aggressiveness is best exemplified by the fact that the peak risk of recurrence is between the first and third years and the majority of deaths occur in the first 5 years following therapy.…”
Section: S Badve Et Almentioning
confidence: 99%
See 1 more Smart Citation